The relation of intima-media thickness with endothelial function and left ventricular mass Index - Korkmaz, Hasan; Akbulut, Mehmet; Ozbay, Yilmaz; Koc, Mustafa (Turkish Soc Cardiology, 2010)
Objective: We aimed to investigate the relation of brachial artery intima-media thickness (IMT) with endothelial function and left ventricular mass (LVM). Methods: Fifty four stage I-II hypertensive patients according to JNC VII who were not taking any medication and 27 age and sex-matched healthy controls were included to this cross-sectional observational study. IMT was measured by the same radiologist who was unaware of the patient's clinical status by using high resolution ultrasound machine. Endothelial function was evaluated by flow mediated dilation (endothelium-dependent vasodilatation, FMD). LVM was calculated by using Devereux method. LVM index (LVMI) was obtained by dividing LVM to body surface area. Mann-Whitney U test was used to compare continuous variables, qualitative variables were compared by Chi-square test and the relations of parameters were evaluated by multiple linear regression analysis. Results: Both groups (hypertensive and control) were similar with respect to age, sex, left ventricular ejection fraction. IMT was significantly higher in hypertensive group (0.43 +/- 0.09 vs 0.33 +/- 0.06 mm; p<0.001). FMD values were also significantly different between hypertensive and control groups (4 +/- 4% vs 13 +/- 12%; p<0.001). LVMI was significantly different between hypertensive and control groups LVMI (124 +/- 5 vs 99 +/- 6 gr/m(2), p=0.002). The correlation between IMT and FMD (r=0.260; p=0.026) and IMT and LVMI (r =0.348; p=0.004) were statistically significant. A correlation was found between IMT and LVMI independently of other variables (beta=105; p=0.004) when LVMI was accepted as dependent variable in multivariate linear regression analysis (R-2=0.570, p<0.001). According to this finding, the 105 units increase in LVMI occurs when IMT increases by 1 mm. Conclusion: Brachial artery IMT is related to endothelial function and LVM. According to these data, any negative changes of the IMT may reflect the similar negative changes in other parameters. (Anadolu Kardiyol Derg 2010; 10:220-5)
Brakiyal arter intima-media kalinli?inin endotel fonksiyonu ve sol ventrikül kütle indeksi ile ilişkisi
Keywords: Intima-media thickness; endothelial function; flow-mediated dilatation; left ventricular mass